2022
DOI: 10.1111/1365-2656.13784
|View full text |Cite
|
Sign up to set email alerts
|

Symmetries and asymmetries in the topological roles of piscivorous fishes between occurrence networks and food webs

Abstract: 1. Ecological networks represent the architecture over which diversity is assembled. The compartmentalization of trophic links and the spatial aggregation of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…Our results confirm the dominance of weak interactions in the food webs of the Paraná River, but also highlight that the biases toward weak interactions is tightly associated with community richness. In addition, the presence of inter-modular connections by species feeding in alternative compartments of food webs, which is theoretically supported as a stabilizing property and has been progressively reported in different ecosystems (McCann 2011;McMeans et al 2016, Borzone Mas et al 2022, was found to significantly increase with diversity in our study. This relationship could arise as a byproduct of the increase in modularity, which makes it more likely for predators to capture prey from different modules.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Our results confirm the dominance of weak interactions in the food webs of the Paraná River, but also highlight that the biases toward weak interactions is tightly associated with community richness. In addition, the presence of inter-modular connections by species feeding in alternative compartments of food webs, which is theoretically supported as a stabilizing property and has been progressively reported in different ecosystems (McCann 2011;McMeans et al 2016, Borzone Mas et al 2022, was found to significantly increase with diversity in our study. This relationship could arise as a byproduct of the increase in modularity, which makes it more likely for predators to capture prey from different modules.…”
Section: Discussionsupporting
confidence: 85%
“…In its middle reach, the Paraná River has an extensive floodplain with a high diversity of microhabitats and a vast fish species richness (Marchetti et al 2013; Scarabotti et al, 2017). The marked thermal seasonality and hydrological variability of the Parana River deeply modify the environmental heterogeneity, the riverscape connectivity, the composition of the communities and the interaction networks (Scarabotti et al 2017; Borzone Mas et al 2022). This combination of biodiversity, spatial heterogeneity, and temporal variability makes the Middle Paraná River an interesting model to test hypotheses about the relationship among diversity, food web structure, and ecosystem functioning (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations